Work-Related Musculoskeletal Disorders Among Libyan Dentists - Koushada, Safa; Thurai Athwair,; Nada Hweissa,; Doha Krema,; Nehal Alfoorjani,; Farah Albeshty, (AlQalam Journal of Medical and Applied Sciences, 2026)
Musculoskeletal disorders are common in dentistry due to repetitive hand movements and sustained static working postures. These conditions often lead to chronic pain and reduced productivity. In Libya, musculoskeletal problems are the most frequently reported occupational health complaint among dentists, yet detailed information, particularly regarding gender and age, is still limited. This study aimed to estimate the prevalence and anatomical distribution of WMSDs among dentists in Western Libya and examine their associations with gender and age. A cross-sectional survey was conducted among 126 dentists employed in public and private clinics. Data were collected using self-administered questionnaires that included demographic and professional characteristics, as well as the Nordic Musculoskeletal Questionnaire. Participants were predominantly female (61.1%) and largely in their early to mid-career years. Over 70% of the participants reported WMSD symptoms in at least one body region in the previous year. The most frequently affected areas were the neck (73.8%), lower back (62.7%), and shoulders (50.0%), followed by the wrists/hands (37.3%) and upper back (34.1%). Neck, lower back, and wrist/hand symptoms prevented normal work in 64.5%, 60.8%, and 61.7% of affected dentists, respectively. Approximately 40%–45% of individuals with neck or lower back pain reported experiencing symptoms in the week preceding their assessment. The overall prevalence did not differ significantly by gender or age, although mid-career dentists reported a greater impact on functional capacity in Western Libya. WMSDs are widespread and frequently persistent, placing substantial strain on dentists and limiting their ability to carry out their professional responsibilities effectively. Most evident in the cervical, lumbar, and upper-extremity regions. The findings underscore the necessity for context-specific ergonomic measures, early preventive education, and ongoing occupational health support to promote healthy practice.